Animal models in neuroscience with alternative approaches: Evolutionary, biomedical, and ethical perspectives - Neziri, Sabina; Koseoglu, Ahmet Efe; Koseoglu, Gulsum Deniz; Ozgultekin, Buminhan; Ozgenturk, Nehir Ozdemir (WILEY, 2024)
Animal models have been a crucial tool in neuroscience research for decades, providing insights into the biomedical and evolutionary mechanisms of the nervous system, disease, and behavior. However, their use has raised concerns on several ethical, clinical, and scientific considerations. The welfare of animals and the 3R principles (replacement, reduction, refinement) are the focus of the ethical concerns, targeting the importance of reducing the stress and suffering of these models. Several laws and guidelines are applied and developed to protect animal rights during experimenting. Concurrently, in the clinic and biomedical fields, discussions on the relevance of animal model findings on human organisms have increased. Latest data suggest that in a considerable amount of time the animal model results are not translatable in humans, costing time and money. Alternative methods, such as in vitro (cell culture, microscopy, organoids, and micro physiological systems) techniques and in silico (computational) modeling, have emerged as potential replacements for animal models, providing more accurate data in a minimized cost. By adopting alternative methods and promoting ethical considerations in research practices, we can achieve the 3R goals while upholding our responsibility to both humans and other animals. Our goal is to present a thorough review of animal models used in neuroscience from the biomedical, evolutionary, and ethical perspectives. The novelty of this research lies in integrating diverse points of views to provide an understanding of the advantages and disadvantages of animal models in neuroscience and in discussing potential alternative methods. Animal models have played a key role in neuroscience research for years. Nevertheless, their usage brings up ethical and transability issues concerning humans. In the recent years, alternative approaches have been developed, containing a potential for replacement and reduction of animal experimenting, associated with more relatable results. This review covers the role the animal models have played so far, the ethical issues, and new replacing technologies.image
Keywords: alternatives; animal models; biomedicine; ethics; evolution; neuroscience; CAENORHABDITIS-ELEGANS; ALZHEIMERS-DISEASE; NEURAL DEVELOPMENT; IN-VITRO; SYNAPTIC-TRANSMISSION; PARKINSONS-DISEASE; NONHUMAN-PRIMATES; CLINICAL-TRIALS; NERVOUS-SYSTEM; BRAIN; Biochemistry & Molecular Biology; Research & Experimental Medicine